School-Based Healthcare and Absenteeism: Evidence from Telemedicine - Sarah Komisarow; Steven W. Hemelt (Institute of Labor Economics (IZA), 2023)
The prevalence of school-based healthcare has increased markedly over the past decade. We study a modern mode of school-based healthcare, telemedicine, that offers the potential to reach places and populations with historically low access to such care. School-based telemedicine clinics (SBTCs) provide students with access to healthcare during the regular school day through private videoconferencing with a healthcare provider. We exploit variation over time in SBTC openings across schools in three rural districts in North Carolina. We find that school-level SBTC access reduces the likelihood that a student is chronically absent by 2.5 percentage points (29 percent) and reduces the number of days absent by about 0.8 days (10 percent). Relatedly, access to an SBTC increases the likelihood of math and reading test-taking by between 1.8- 2.0 percentage points (about 2 percent). Heterogeneity analyses suggest that these effects are driven by male students. Finally, we see suggestive evidence that SBTC access reduces violent or weapons-related disciplinary infractions among students but has little influence on other forms of misbehavior.
Keywords: I10; I21; 330; school-based healthcare; student absences; telemedicine